INOVASI MODEL-MODEL PEMBELAJARAN BIDANG SAINS UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA - Muh Khalifah Mustami (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2009)
The teachers of science should develop teaching process by making innovation on different models of teaching. It is designed to get students interest and develops innovative thinking for a maximum end. With respect to teaching science, teachers should employ analo-gical approach, use multimedia, and technology based teaching. In addition, the qualification of academics, students, teaching facilities, teaching process, curriculum and controlling are of great importance for effective learning process.